Granulocyte colony-stimulating factor expression from transduced vascular smooth muscle cells provides sustained neutrophil increases in rats - Lejnieks, D. V.; Han, S. W.; Ramesh, N.; Lau, S.; Osborne, WRA (Mary Ann Liebert, Inc., 1996)
Granulocyte colony-stimulating factor (G-CSF) regulates granulocyte precursor cell proliferation, neutrophil survival, and activation. Cyclic hematopoiesis, a disease that occurs both in humans and grey collie dogs is characterized by cyclical variations in blood neutrophils. Although the underlying molecular defect is not known, long-term daily administration of recombinant G-CSF eliminates the severe recurrent neutropenia, indicating that expression of G-CSF by gene therapy would be beneficial. As a prelude to preclinical studies in affected collie dogs, we monitored hematopoiesis in rats receiving vascular smooth muscle cells transduced to express G-CSF. Cells transduced with LrGSN, a retrovirus expressing rat G-CSF, were implanted in the carotid artery and control animals received cells transduced with LASN, a retrovirus expressing human adenosine deaminase (ADA). Test animals showed significant increases in neutrophil counts for at least 7 weeks, with mean values of 3,670 +/- 740 cells/mu l in comparison to 1,870 +/- 460 cells/mu l in controls (p < 0.001). Thus, in rats G-CSF gene transfer targeted at vascular smooth muscle cells initiated sustained production of 1,800 neutrophils/mu l, a cell number that would provide clinical benefit to patients. Lymphocytes, red cells and platelets were not different between control and test animals (p > 0.05). These studies indicate that retrovirally transduced vascular smooth muscle cells can provide sustained clinically useful levels of neutrophils in vivo.